2006
DOI: 10.1093/protein/gzl011
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of an albumin-binding Fab (AB.Fab) can be modulated as a function of affinity for albumin

Abstract: An AB.Fab (albumin-binding Fab) consists of a Fab and a phage-derived albumin-binding peptide. This molecule is capable of binding both antigen and albumin simultaneously. Using a Fab derived from Herceptin we generated a panel of AB.Fab variants with wide-ranging affinities for albumin. An assay that measured AB.Fab binding to albumin in solution was developed to most accurately reflect the binding affinity for albumin in vivo. Affinity varied depending upon the species of albumin tested. For rat and rabbit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 1 publication
5
101
0
1
Order By: Relevance
“…The VHH sequences are flanked by two E-tag peptides (underlined) and separated by an unstructured spacer ((GGGGS) 3 ). A 14-amino acid albumin binding peptide (ABP), DICLPRWGCLEWED (36), is at the carboxyl end, separated from the second E-tag by a GGGGS spacer. For clarity, the eight defined protein segments are separated by slashed (///).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VHH sequences are flanked by two E-tag peptides (underlined) and separated by an unstructured spacer ((GGGGS) 3 ). A 14-amino acid albumin binding peptide (ABP), DICLPRWGCLEWED (36), is at the carboxyl end, separated from the second E-tag by a GGGGS spacer. For clarity, the eight defined protein segments are separated by slashed (///).…”
Section: Resultsmentioning
confidence: 99%
“…We have found that VHH heteromultimer VNAs possess additional potential therapeutic advantages over conventional mAb products such as 1) the option to co-administer an anti-tag effector antibody that binds multiple tags on the VNAs (11,13) to promote antibody Fc effector functions such as serum clearance (33), 2) the ability to target multiple toxins with one biomolecule (12,16), and 3) the use of VNA gene therapy as an effective means to provide prolonged antitoxin protection (34,35). Simple addition of an albumin binding peptide (34,36) can dramatically improve the serum stability of VNAs (34). Because VHHs can be obtained from preexisting libraries (37) and then affinity-matured for improved properties (38,39), new antitoxins can be rapidly developed as treatments for emerging threat agents.…”
Section: Discussionmentioning
confidence: 99%
“…PEGylated interferon ␣-2a (PegIntron, PEGASYS) and PEGylated granulocyte-colony stimulating factor (Neulasta), or are under clinical development, e.g. a PEGylated anti-TNF Fab fragment (certolizumab pegol) (9, 12) Furthermore, direct fusion to albumin or an albumin binding moiety, such as albumin-binding peptides or bacterial albuminbinding domains, was applied to improve pharmacokinetics of therapeutic proteins including interferon-␣, interleukin-2, insulin, Fab fragments, and recombinant bispecific antibody molecules (4,8,(13)(14)(15). This strategy is based on the observation that albumin has a similar half-life as IgG and also utilizes FcRn-mediated recycling processes.…”
mentioning
confidence: 99%
“…With the advent of recombinant protein expression and efficient in vitro selection technologies, this novel class of engineered protein scaffolds presents attractive opportunities for both diagnostic and therapeutic use. If longer serum half-lives are required, this could be achieved by site-specific PEGylation (15) or by hijacking an abundant serum protein with a long half-life, like albumin or immunoglobulin G through peptide tags that bind to them to escape glomerular filtration (46,47). Knowing the recent set backs of human anti-A␤ therapies, this study opens new avenues away from antibodies toward DARPins to fight brain amyloidosis effectively.…”
Section: Discussionmentioning
confidence: 99%